Social protection to combat hunger - Wouterse, Fleur; Murphy, Sophia; Porciello, Jaron (Nature Publishing Group, 2020)
COVID-19 and the measures governments have put in place to prevent its aggravation have triggered an economic recession that will increase poverty rates and hunger. In June, the International Monetary Fund projected a 4.9% decline in global economic growth compared to 20191. A similar forecast has been generated under Ceres2030, a research project co-directed by the International Food Policy Research Institute, Cornell University and the International Institute for Sustainable Development that is calculating the cost of effective interventions to end hunger sustainably. The estimate is that 95 million additional people, mostly from sub-Saharan Africa, will be living in extreme poverty by the end of the year.